Temporary Migration and Wages of Ph.D.s. Stay Longer or Come Back Sooner? - Di Cintio, Marco; Grassi, Emanuele (Review of Economic Analysis, 2025)
This paper examines the wage implications of temporary migration for two cohorts of Italian Ph.D.s. Special attention is given to the duration of the international experience, its contribution to earned wages and the selectivity of returnees. Returnees are found to be a self-selected group whose unobservable characteristics are simultaneously associated with both higher wages and a higher propensity to migrate. Moreover, we find positive returns for those who stay longer and negative returns for those who come back sooner. The results are confirmed in several robustness and sensitivity checks.